Enzymatic retting of Piper nigrum L. using commercial Pectinase(Peelzyme) - Dayang Syahreeny, Abang Mustafa; Azham, Zulkharnain; Awang Ahmad Sallehin, Awang Husaini (Journal of Chemical and Pharmaceutical Sciences, 2015)
White peppers produced from Piper nigrum L. retted with different concentration of commercial pectinase (PeelZyme) and blanching treatment in hot water were compared. The effects of these treatments on surface morphology and piperine content of white berries was studied. PeelZyme at the concentration of 500 ppm successfully produced white berries after 5 days. However, white berries retted with PeelZyme at the concentration of 500 ppm without blanching gave the best surface morphology but there was a reduction in the piperine content by 3.04%. Blanching in hot water resulted in reduction of surface quality but an increase of piperine content up to 40% was obtained.